CONTENT AND PRINCIPLES OF ECONOMIC HARMONIZATION OF INTERESTS OF INDUSTRIAL ENTERPRISES - М.М. Климчук; А.Д. Кухарук; Т.В. Іванова; К.Ю. Редько (Ekonomìčnij Vìsnik Nacìonalʹnogo Tehnìčnogo Unìversitetu Ukraïni "Kiïvsʹkij Polìtehnìčnij Institut", 2023)
The article is devoted to the problems of harmonizing the economic interests of enterprises under the conditions of destabilizing factors of the external environment. The theoretical basis of the research is the work of foreign and domestic scientists. The study is based on a systems approach, the economic theory of development based on resources, and the theory of economic harmonies. The content of the concept of "harmonization of the economic interests of the enterprise" is defined, under which it is proposed to understand the process of harmonizing the economic interests of the enterprise and the interests of other subjects of the external environment, which provides for the reduction of the imbalance in the resource provision of all market participants and enables the further commercially successful activity of the enterprise on the basis of innovative activity, corporate social responsibility, and sustainable development. The following principles of harmonizing the interests of industrial enterprises are highlighted: complexity, planning, limitations, competitiveness, environmental friendliness, balance, continuity, and efficiency. The obtained results deepen scientific developments regarding the need for economic harmonization of domestic industrial enterprises. The structure of the balance sheet of economic entities in Ukraine for the period 2019-2021 is shown. The types of economic activity characterized by the dominance of the share of non-current assets in the total assets of the respective enterprises are highlighted. The need to consider the dependence of businesses on material costs when determining ways to harmonize their economic activity is emphasized. Areas of ensuring the harmonization of economic interests of economic entities are highlighted, namely: innovative cooperation; optimization preservation and focusing strategy; digitalization of business.